AI in the workplace : who is using It and why? ; A look at the driving forces behind artificial intelligence in German companies - Gerhards, Christian [Verfasser]; Baum, Myriam [Verfasser] (My University, 2024)
"We examine the spread and usage of artificial intelligence (AI) in German companies. The study analyses which company characteristics favor or inhibit the adoption of AI. Hypotheses are developed that include factors such as the type of tasks, level of innovation, degree of digitalization, company size, and industry affiliation. Empirical data from the BIBB Qualification Panel shows that AI usage is slowly but steadily increasing, particularly in larger and more innovative companies. The multivariate analysis highlights that an advanced digital infrastructure and an innovative corporate culture are crucial for AI integration. The findings aim to support political and strategic decision-making processes and to promote the implementation of AI in companies, while considering ethical implications." (Authors‘ abstract; BIBB-Doku)
Keywords: S 3.2 Unternehmen und Behörden; L 4.2 Mediengestützte Lehr-Lernformen; 370; Unternehmen; Unternehmenskultur; Medieneinsatz; Einflussfaktor; Künstliche Intelligenz; BIBB-Qualifizierungspanel